Roles of human papillomavirus infection and stathmin in the pathogenesis of sinonasal inverted papilloma. Issue 2 (22nd May 2015) - Lin, Hai; Lin, Dong; Xiong, Xi‐Sheng
ABSTRACT: Background: The purpose of this study was to investigate roles of human papillomavirus (HPV) infection and stathmin in sinonasal inverted papilloma (SNIP). Methods: HPV DNA detection was performed by the fluorescence‐based polymerase chain reaction (PCR) method. Stathmin protein expression was investigated by the immunohistochemistry method and mRNA expression of stathmin, Kif2a, and cyclin D1 were assessed by real‐time PCR in SNIP and control subjects. Results: The positive rate of HPV DNA detected in SNIP was about 53.6% (15 of 28). Recurrent cases showed a higher rate of HPV infection compared with initial cases and higher Krouse stage (T3 + T4) cases showed higher rate of HPV infection than lower Krouse stage (T1 + T2) cases. Stronger expression of stathmin, Kif2a, and cyclin D1 were observed in SNIP, especially HPV(+) SNIP. Conclusion: HPV infection was closely associated with recurrence and progression of SNIP. Stathmin is a valuable prognostic marker and could be considered as a therapeutic target in patients with SNIP. © 2015 Wiley Periodicals, Inc. Head Neck 38: 220–224, 2016